Opportunistic Pulmonary Infections in Immunocompromised Hosts. Issue 2 (April 2016) - Rali, Parth; Veer, Manik; Gupta, Nupur; Singh, Anil C.; Bhanot, Nitin
Abstract : Infections that are typically innocuous in immunocompetent persons may cause significant disease states in immunocompromised hosts. These individuals may be immunosuppressed secondary to many different causes such as drugs, malignancy, solid-organ or hematopoietic stem cell transplantation, HIV/AIDS, or anatomic reasons (asplenia). These immunocompromised hosts are at high risk for developing opportunistic infections. Here, we discuss some of these infections caused by bacteria, fungi, viruses, and parasites. Clinicians should be aware of the risk factors, common clinical presentations, diagnostic modalities, and treatment options for these potentially fatal illnesses.